Investigation of Laboratory Experimental Methods for Determining the Acceleration Constant (g) and Comparison with Theoretical Values in Kabul - Khawari, Rajab Ali (Journal of Natural Sciences – Kabul University, 2022)
This research aims to identify the most accurate laboratory method for determining the acceleration due to gravity (g) at a specific location. Data were collected using four laboratory methods to measure g in the physics laboratory. The results from these methods were compared with theoretical values, and the most effective method was identified as the physical pendulum approach. The experimental value obtained for g in Kabul was gexp=978.767 cm/s2g_{\text{exp}} = 978.767 \, \text{cm/s}^2gexp​=978.767cm/s2, which differs by 0.3 from the theoretical value of gthe=978.4986 cm/s2g_{\text{the}} = 978.4986 \, \text{cm/s}^2gthe​=978.4986cm/s2. The experimental error was 0.3%, which is within the permissible range of laboratory instrument and calculation errors.